O potencial de matéria escura na evolução dinâmica de galáxias esferoidais anãs - Castro, Matheus Marques de (2020)
All classic dwarf spheroidal galaxies are characterized by a low amount of neutral gas, however the processes responsible for the removal of their gaseous content are still debated in the literature, these mechanisms responsible for the removal can have internal origin (stellar feedback) and external (ram pressure, tidal stripring) or even a combination of the two effects. Regardless of the mechanism acting on the loss of gas, the gravitational potential of the galaxy plays an important role in this process, acting in the opposite direction to the loss. An important component in the gravitational potential of dwarf galaxies is the dark matter halo, which dominates it. In order to understand how the gaseous content of spheroidal dwarf galaxies is removed, non-cosmological three-dimensional hydrodynamic simulations were applied to a model galaxy (the dwarf spheroidal galaxy Ursa Minor - UMi) adopting different scenarios for the mass of the dark matter halo. The effects of this potential on the dynamic evolution of the interstellar medium of the galaxy was analyzed taken into account the feedback from type II and type Ia supernovae and the outflow of an intermediate-mass black hole (IMBH), separately. The results indicate that, in addition to making the mass loss difficult, decreasing the amount of gas lost at the end of the simulation, the cases with more massive dark matter halos also influence the distribution of the initial gas density and the spatial distribution of the supernovae type II in time and do not allow the outflow to impact the galactic medium and the formation of a jet feature. At the end of the simulation that takes into account only the supernovae feedback, the case with Mh = 3, 05 × 109 M loses approximately 8 times more gas than the case with Mh = 1, 82 × 1010 M.